2019
DOI: 10.1097/md.0000000000018146
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial diameter in heart failure with left ventricular preserved, mid-range, and reduced ejection fraction

Abstract: Left atrial (LA) remodeling has been identified to predict atrial fibrillation (AF) and heart failure. However, the role of LA diameter (LAD) in patients with heart failure (HF) with preserved (HFpEF), mid-range (HFmrEF), and reduced ejection fraction (HFrEF) remains poorly understood. A total of 142 patients including 71 subjects with AF (21 of HFpEF, 22 of HFmrEF, and 28 of HFrEF) and 71 ejection fraction (EF)-matched subjects with sinus rhythm (SR) were included in the study. Baseline characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Most human HFrEF RNA-Seq studies were focused on regional changes within the LV. HFrEF-related gene expression changes in other heart chambers have not been thoroughly explored, despite the known clinical link between the left atrium (LA) and HFrEF prognosis 19 , 20 . Recent advances and application of single cell technology in cardiac tissues have revealed cellular expression network heterogeneity and led to novel insights of cardiac physiology and pathology 11 13 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Most human HFrEF RNA-Seq studies were focused on regional changes within the LV. HFrEF-related gene expression changes in other heart chambers have not been thoroughly explored, despite the known clinical link between the left atrium (LA) and HFrEF prognosis 19 , 20 . Recent advances and application of single cell technology in cardiac tissues have revealed cellular expression network heterogeneity and led to novel insights of cardiac physiology and pathology 11 13 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In the multivariate regression analysis, one of the independent predictors of fQRS was the LAD. Atrial dilatation, which is a sign of left atrial remodeling and diastolic dysfunction, has been shown to be associated with many cardiovascular diseases such as atrial fibrillation and heart failure [39,40]. Therefore, those with fQRS may have greater myocardial dysfunction, and these patients should be followed more closely to prevent the development of advanced acromeglic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[1] and Eq. [2] (see above) into software, input t1-t2, t1-t3, which could automatically calculate LAP ECHO . LAP ECHO was calculated for 3 consecutive cardiac cycles, and the average value was selected for the statistical analysis.…”
Section: Lap Echo Calculationmentioning
confidence: 99%
“…Currently, a variety of non-invasive methods for evaluating LAP, such as the "Doppler + sphygmomanometer" method have been explored. Due to their inaccuracy and complexity, these methods have not been used in clinical practice (2,3).…”
Section: Introductionmentioning
confidence: 99%